2017
DOI: 10.1177/1525740117728475
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Autism Research With Children Who Are Deaf or Hard of Hearing

Abstract: Autism Spectrum Disorder (ASD) is a developmental disability characterized by impairments in social communication and language as well as restricted and repetitive interests and behaviors (American Psychiatric Association, 2013). The prevalence of ASD is increasing and currently affects as many as one in 68 children and one in 46 males (Centers for Disease Control and Prevention, 2016). Children with ASD require supports for success in school and other settings (Bond et al., 2016; Shire et al., 2015). Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…While previous studies have primarily focused on clinical features and challenges with diagnosis (Shield, 2014), with very few studies examining ASL acquisition or improvement (Scott & Dostal, 2019; Shield, 2014), no studies to date have examined potential modifications or adaptations to ABA intervention that may be required to meet the needs of DHH autistic children. The results of the current study support previous findings suggesting that adaptations and modifications to existing evidence‐based practices are needed to meet the unique needs of DHH autistic children (Hansen & Scott, 2018; Nelson & Bruce, 2019; Szarkowski et al., 2014). We utilized adapted behavior analytic procedures in collaboration with an ASL interpreter to improve language and communication skills for a young child with dual diagnoses of DHH and ASD.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…While previous studies have primarily focused on clinical features and challenges with diagnosis (Shield, 2014), with very few studies examining ASL acquisition or improvement (Scott & Dostal, 2019; Shield, 2014), no studies to date have examined potential modifications or adaptations to ABA intervention that may be required to meet the needs of DHH autistic children. The results of the current study support previous findings suggesting that adaptations and modifications to existing evidence‐based practices are needed to meet the unique needs of DHH autistic children (Hansen & Scott, 2018; Nelson & Bruce, 2019; Szarkowski et al., 2014). We utilized adapted behavior analytic procedures in collaboration with an ASL interpreter to improve language and communication skills for a young child with dual diagnoses of DHH and ASD.…”
Section: Discussionsupporting
confidence: 87%
“…For example, instruments to detect ASD in DHH children do not yet exist, and interventions that are tailored to meet the needs of this unique population have been rarely studied (Szarkowski et al., 2014). Given the complexity among this population, there is a pressing need for high‐quality research involving individuals with dual diagnoses of both ASD and DHH (Hansen & Scott, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is the first validation of a parent semi-structured interview to assess for ASD in a deaf population. Against a backdrop of limited research in this field (Hansen & Scott, 2018), this provides a very welcome addition for clinical practice. Our findings indicate that the ADI-R Deaf Adaptation is a valid measure for use in the deaf child population in the UK context, no matter what languages or communication methods they use.…”
Section: Discussionmentioning
confidence: 99%
“…There have been very few studies investigating ASD in deafness (Quinto-Pozo et al 2011 ; Hansen and Scott 2018 ). Studies of communication skills in deaf children with ASD have identified characteristics of their communication equivalent to those found in hearing children with ASD (Scawin 2003 ; Shield and Meier 2012 ; Szymanski et al 2012 ; Shield et al 2015 , 2016 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%